The Effect of Dynamic Capabilities on High Performance: An Analytical Study of Administrative Units in Anbar Governorate - Ibraheem, Hakeem Khalill; Mhaibes, Hussam Ali Mhaibes (Journal of Economics and Administrative Sciences, 2025)
The present study analyses the impact of dynamic capabilities on the high performance that can be developed in administrative units under the Anbar Governorate of Iraq. Sensing, learning, coordinating, and integrating capabilities are dynamic capabilities that actually represent the organization’s capacity to adjust itself to changing environments and its sustainable growth. High-performance organization could be reflected through continuous improvement, quality management, excellence in human resources, orientation, and commitment, considering it the measures of organizational effectiveness in reaching strategic objectives. Research shows that the dynamic capabilities and high performance of the administrative units studied were at moderate levels. The results of the findings disclosed the existence of a significant positive relationship between dynamic capabilities and high performance, since it was revealed that dynamic capabilities such as proactive sensing of opportunities and challenges, coordinated efforts, and continuous learning directly improve organizational performance outcomes. Along this line, therefore, this highlights the importance of developing dynamic capabilities by focusing administrative units’ attention on training, resource integration, innovative practices, and the like. Exploring some of the issues concerning these unit’s limited coordination and learning will improve organizational adaptability through better resource utilization and improved service delivery to their local communities, thereby enhancing high performance.